Between State and Non-State
XI, 278 p. 2 illus.
Keywords: This edited volume compares the internal dimension, politics and society in Kurdistan-Iraq and Palestine. In particular, it focuses on internal processes in Kurdistan-Iraq and Palestine (Palestinian Territory of the West Bank and Gaza Strip) in their specific shaping, development and transformation. The contributing authors analyze the transformation processes of the internal power structures, the economic basics, and the civil societies and provide an overview of the current political, economic and societal situation and challenges in both regions. The book presents the similarities and differences between both de facto states with regard to a set of guidelines: legitimacy, power relations, transformation of politics and society. It provides empirical explanations and contributes to a better understanding of both de facto states.